Insularisation and lifestyle migration on the island of Hvar - Perinić Lewis, Ana (Svetovi (Ljubljana), 2025)
The paper analyses lifestyle migration on the island of Hvar through the lens of an ethnographic approach. The diversity of migratory experiences among the interviewees, who were interviewed for the purposes of this research, is examined through the concept of insularisa-tion, approached as a profoundly ambivalent phenomenon encompassing both distancing and isolation, as well as the need for connection and integration into the rhythm of island communities. Through the concept of insularisation, the authors explore the discrepancy between imagined ideas about islands and their Mediterranean identity, and the practical experiences of lifestyle migrants, which highlight various obstacles and challenges. This approach enables a more nuanced understanding of the concept of lifestyle migration and the connections formed with the notion of islandness.
Keywords: Croatia; ethnographic approach; ethnology; etnografski pristop; etnologija; Hrvaška; Hvar; insularisation; island of Hvar; lifestyle migration; Mediterranean; migracije zaradi spremembe življenjskega sloga; otočenje; Sredozemlje